Old views in Lambeth : 1. Carlise House. : 2. Entrance to Cuper's Gardens. : 3. Remains of Orchestra, Cuper's Gardens. : 4. Conspirators' House. - Prior, William Henry (Tufts Archival Research Center, 2006)
This illustration is from Edward Walford "Old and new London, a narrative of its history, its people, and its places, vol. 6"